Host and Non-host 'Whistle Stops' for Psyllids: Molecular Gut Content Analysis by High-Throughput Sequencing Reveals Landscape-Level Movements of Psylloidea (Hemiptera). Issue 3 (1st May 2019) - Cooper, W Rodney; Horton, David R; Wildung, Mark R; Jensen, Andrew S; Thinakaran, Jenita; Rendon, Dalila; Nottingham, Louis B; Beers, Elizabeth H; Wohleb, Carrie H; Hall, David G; Stelinski, Lukasz L
Abstract: Psyllids (Hemiptera: Psylloidea) are phloem-feeding insects that tend to be highly specific in their host plants. Some species are well-known agricultural pests, often as vectors of plant pathogens. Many pest psyllids colonize agricultural fields from non-crop reproductive hosts or from non-host transitory and winter shelter plants. Uncertainty about which non-crop species serve as sources of psyllids hinders efforts to predict which fields or orchards are at greater risk of being colonized by psyllids. High-throughput sequencing of trnL, trnF, and ITS was used to examine the dietary histories of three pest and two non-pest psyllid species encompassing a diversity of lifecycles: Cacopsylla pyricola (Förster) (Psyllidae), Bactericera cockerelli (Šulc) (Triozidae), Diaphorina citri Kuwayama (Liviidae), Aphalara loca Caldwell (Aphalaridae), and a Cacopsylla species complex associated with Salix (Malphighiales: Salicaceae). Results revealed an unexpectedly high level of feeding on non-host species by all five psyllid species. The identification of the dietary history of the psyllids allowed us to infer their landscape-scale movements prior to capture. Our study demonstrates a novel use for gut content analysis—to provide insight into landscape-scale movements of psyllids—thus providing a means to pinpoint the non-crop sources of pest psyllids colonizing agricultural crops. We observed previously unknown psyllid behaviors during our efforts to develop this method and discuss new research directions for the study of psyllid ecology.